A review of the in-situ capping amendments and modeling approaches for the remediation of contaminated marine sediments - Labianca, Claudia; De Gisi, Sabino; Todaro, Francesco; Notarnicola, Michele; Bortone, Imma (Elsevier, 2021)
Contaminated sediments can pose long-term risks to human beings and ecosystems as they accumulate inorganic and organic contaminants becoming a sink and source of pollution. Compared to ex-situ technologies (i.e., dredging activities and off site treatments), in-situ capping (ISC) intends to minimize contaminated sediment mobilization and impact into the water column whilst treating contamination. Literature shows that numerous types of ISC amendments in presence of both organic and inorganic pollutants are investigated, although a few are contributions whose experiments have been designed and conducted with a view to future engineering. Against this background of shortcomings, this review paper intends to investigate ISC reliability, applicability and its long-term effectiveness, by also comparing reactive and physical ISCs. Additionally, an examination of the main numerical simulations applied to ISC technology was carried out. We found that activated carbon and organoclay resulted the most studied amendments for organically contaminated sediment, whereas biochar, clay minerals, and industrial-by products were more employed in presence of sediment contaminated by metal(loids). There is no better ISC system in absolute terms, since technological performance depends on many factors and only a few experimental investigations included a long-term modeling phase to predict ISC long-term efficiency. Most of numerical models included simplified transport equations based on diffusion and adsorption, and the goodness of fitting between experimental and modeled data was not always computed. The review finally discusses new research directions such as the need for long-term applications on field-scale and cap effectiveness in presence of site-specific tidal forces and currents.
Keywords: Adsorption; Contaminant fate and transport; Long-term simulation; Organic and inorganic pollution; Environmental remediation